Quality Analysis Of Islamic Religious Education Learning Questions At Smkn 1 Meulaboh Through Anates Software - Rahmad Syah Putra; Zubaidah; Muhammad Furqan (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This study is a quantitative study to analyze the quality of Islamic Religious Education (PAI) Learning questions at State Vocational High School (SMKN) 1 Meulaboh, Aceh Barat Regency using Anates software. The object of the study was SMKN Class XI (eleven) students in the Even Semester of the 2023/2024 Academic Year. The data collection technique used was the documentation technique, namely to obtain exam question data, answer keys and answer sheets for all exam participants. Then for the item analysis process, it was carried out using the Anates Software Application Version 4.0.9, where the program would analyze the questions in terms of validity, reliability, level of difficulty, discriminating power and effectiveness of distractors which would then conclude the quality of the questions. The results of the research that has been carried out show that there are five question items categorized as very easy. Of the five question items, only one question item has the easiest level of difficulty, namely 0.92, has a discriminating power of 0.20 and two distractors do not function. And one item has the most difficult level of difficulty, which is 0.05 and the discriminating power of the question is 0.00. The five questions are recommended to be improved and only one item cannot be used because it has a very low level of discriminating power. Thus, it can be concluded that the quality of the questions presented is good, although there are 5 items that need to be improved in quality.